John Alden; steadfast Pilgrim. - Edwards, Cecile Pepin; Orr, Forrest W. (Boston Houghton Mifflin, 1965)
A biography of the cooper who joined the Pilgrim church and became on of the leaders of Plymouth Colony.
Keywords: Alden, John -- 1599-1687. -- Juvenile literature; Alden, John -- 1599-1687.; Pilgrims (New Plymouth Colony) -- Biography -- Juvenile literature; Pilgrims (New Plymouth Colony)